Conventional Wisdom? Analyzing Public Support for a State Constitutional Convention Referendum. (March 2019) - Lewis, Daniel C.; Collens, Jack D.; Cutler, Leonard
Although fourteen American states periodically hold automatic referendums on whether to hold a state constitutional convention, no state has approved a constitutional convention referendum since 1984. This study explores the puzzle of why voters would oppose an opportunity to broadly reform state government and the factors that underlie these attitudes. Analyses of two statewide surveys of registered voters in New York during the 2017 Constitutional Convention Referendum campaign reveal that campaign framing, elite cues, and instrumental concerns have led voters to take risk-averse positions in order to minimize potential losses that could result from a constitutional convention.